2012
DOI: 10.12968/bjcn.2012.17.12.614
|View full text |Cite
|
Sign up to set email alerts
|

Extending an approach to hospital malnutrition to community care

Abstract: This feature investigates the potential relevance to community care of a new food provision and nutritional management system for older hospital patients. A qualitative study identified the core factors contributing to inadequate food intake in older patients in hospital, including: poor mealtime ambience; lack of necessary mealtime assistance; inflexible meal provision; lack of monitoring of nutrient intake and absence of accountability in nutritional care. Many of these factors are also relevant to older peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…No intervention addressed the barrier of loneliness. Qualitative studies showed older adults may struggle with cooking [46, 49, 50] and eating alone [51]. A possible solution may be to offer ideas to help patients connect with others, but none of the interventions offered such self-help advice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No intervention addressed the barrier of loneliness. Qualitative studies showed older adults may struggle with cooking [46, 49, 50] and eating alone [51]. A possible solution may be to offer ideas to help patients connect with others, but none of the interventions offered such self-help advice.…”
Section: Resultsmentioning
confidence: 99%
“…through education) or measure reactions to screening. We currently have little data on how older adults perceive screening or why they are reluctant to be screened [48, 49]. Notably, findings relating to patients’ barriers to screening emerged largely from HCPs’ experiences [48, 49, 55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings suggest that the nutrition intervention may have lacked relative advantage over the current menu and compatibility with patients’ appetite, food and size preferences and perspectives on food waste. These barriers to intake have been reported elsewhere . Consequently, foodservice staff felt that patients were resistant towards the higher energy menu.…”
Section: Discussionmentioning
confidence: 57%
“…These barriers to intake have been reported elsewhere. [22][23][24] Consequently, foodservice staff felt that patients were resistant towards the higher energy menu. Lambert et al 19 also report nurses' challenges in encouraging patients to consume ONS.…”
Section: Discussionmentioning
confidence: 99%